Filogeografia global da tartaruga oliva (Lepidochelys olivacea) - Hahn, Anelise Torres (2011)
The first chapter of this thesis is the first study about the olive ridley turtle s (Lepidochelys olivacea) genetic diversity and population structure in Brazil. The olive ridley is the most abundant species of marine turtle and is listed as vulnerable by the IUCN. Olive ridleys had a strong history of harvest in the Atlantic Ocean, with some populations being severely depleted; in Brazil the egg exploitation was intense until before 1982. However, a single study with a very low sample size so far investigated the species´ mtDNA diversity in the region. Herein we characterize the genetic diversity and population structure of the olive ridley nesting populations in the Brazilian coast based on 92 samples sequenced for the mtDNA control region and 67 samples genotyped for fifteen microsatellite loci. Although three mtDNA haplotypes were found, two previously unknown but very rare, the Brazilian nesting population presented one of the lowest mtDNA diversity known for the species. Contrary, our newly described microsatellite data showed moderate to high genetic diversity for olive ridleys from Brazilian nesting sites, similar to the few other nesting populations studied so far, suggesting that the high level of egg harvest in Brazil did not result in a recent genetic bottleneck. mtDNA data indicated a population expansion following a population decline in the past while microsatellite data suggested a scenario of demographic stability, supporting the scenario of colonization of Atlantic Ocean via a founder effect. Since results from both markers present no evidence of significant genetic differences between the studied olive ridleys nesting areas in the Brazilian coast, conservation strategies should consider the Brazilian olive ridleys as a single interbreeding population. The second chapter is a global phylogeographic study of the olive ridley. It was proposed that the ridley turtles diverged after the closure of the Isthmus of Panama during the Pliocene, and then L. olivacea has spread from the Pacific Ocean into the Indo-Pacific, Indian and only recently to the Atlantic Ocean. Genetic analyses have been consistent with this scenario although some authors have proposed the Indo-Pacific region as the center of origin for the ridley turtles instead. To address this and other questions on the population structure patterns and demographic changes through time, we used mtDNA sequence and the STRs for 300 samples of ridley turtles across their range. The olive ridley nesting sites are well structured for the mtDNA, while for STRs the population divergences are lower for regional rookeries but highly significant among oceans, suggesting male-mediated gene flow within oceans. Beyond a kemp s clade, we corroborated the existence of four geographic mtDNA clades for the olive ridleys: the K clade only found in Indian Ocean, and the East Pacific, Indo- Pacific and Atlantic clades. The K clade originated around 1.6 Mya, the East Pacific clade about 0.61 Mya, and the split between the Indo-Pacific and Atlantic lineages around 0.36 Mya. These results are mostly consistent with the recent colonization of East Pacific and the Atlantic and suggest a model of recurrent extinction/colonization for most ridley nesting sites that may be explained by the climatic changes, especially during the Pleistocene. Diversification times within all five clades are very similar, ranging between 221 Kya and 342 Kya, suggesting the most recent demographic events for most oceanic regions may have been concurrent. Significant statistics for the STR data and similarly shaped star trees in each of the four major olive ridley clades suggested a population expansion, a scenario partially corroborated by the Bayesian Skyline Plot analysis which is indicating a population expansion for L. olivacea after the last glacial maximum.